Clinical, microbiological, and immunological effects of fructo-oligosaccharide in patients with Crohn's disease. Issue 3 (14th September 2005) - Lindsay, J O; Whelan, K; Stagg, A J; Gobin, P; Al-Hassi, H O; Rayment, N; Kamm, M A; Knight, S C; Forbes, A
Abstract : Background and aims: The intestinal microbiota play a pivotal role in the inflammation associated with Crohn's disease through their interaction with the mucosal immune system. Some bifidobacteria species are immunoregulatory and induce increased dendritic cell interleukin 10 (IL-10) release in vitro. Fructo-oligosaccharides (FOS) increase faecal and mucosal bifidobacteria in healthy volunteers. The aim of this study was to assess the effect of FOS administration on disease activity, bifidobacteria concentrations, and mucosal dendritic cell function in patients with moderately active Crohn's disease. Patients and methods: Ten patients with active ileocolonic Crohn's disease received 15 g of FOS for three weeks. Disease activity was measured using the Harvey Bradshaw index. Faecal and mucosal bifidobacteria were quantified by fluorescence in situ hybridisation, and mucosal dendritic cell IL-10 and Toll-like receptor (TLR) expression were assessed by flow cytometry of dissociated rectal biopsies. Results: FOS induced a significant reduction in the Harvey Bradshaw index from 9.8 (SD 3.1) to 6.9 (3.4) (p<0.01). There was a significant increase in faecal bifidobacteria concentration from 8.8 (0.9) log10 to 9.4 (0.9) log10 cells/g dry faeces (p<0.001). The percentage of IL-10 positive dendritic cells increased from 30 (12)% to 53 (10)% (p = 0.06). Finally, the percentage of dendritic cells expressing TLR2 and TLR4 increased from 1.7 (1.7)% to 36.8 (15.9)% (p = 0.08) and from 3.6 (3.6)% to 75.4 (3.4)% (p<0.001), respectively. Conclusions: FOS supplementation increases faecal bifidobacteria concentrations and modifies mucosal dendritic cell function. This novel therapeutic strategy appears to decrease Crohn's disease activity in a small open label trial and therefore warrants further investigation.